Existential–Humanistic and Relational Psychotherapy During COVID-19 With Patients With Preexisting Medical Conditions. (July 2021) - Gordon, Robert M.; Dahan, Jacqueline Fine; Wolfson, Joanna B.; Fults, Erin; Lee, Yuen Shan Christine; Smith-Wexler, Lucia; Liberta, Taylor A.; McGiffin, Jed N.
Unexpected traumatic events, including life-threatening medical conditions, brain injuries, and pandemics, can be catalysts for patients and clinicians to consider existential issues, including meaning in life. The existential–humanistic and relational perspectives on therapeutic interventions emphasize creating meaning, taking responsibility for one's own life and self-narratives, choosing and actualizing ways of being in the world that are consistent with values, and expanding the capacity for agency, commitment, and action. Myriad factors have made the COVID-19 pandemic upsetting and potentially traumatic for individuals, including the novel experience of self and other as possibly infectious and dangerous, a sense that anyone is vulnerable, and protracted uncertainty about the duration of the crisis and its consequences. The vignettes included in this article explore risk and reliance factors relevant to patients with preexisting medical conditions during COVID-19 and highlight the benefits of exploring values, priorities, and assumptions, asking open-ended questions about meaning in life and posttraumatic growth, learning for each emotion, and interpretation of dreams. The existential–humanistic and relational approaches offer unique insights into how practitioners might help their patients to reflect on the unanticipated changes and anxieties ignited by COVID-19, while reinforcing the potential to live with greater purpose and intention.